Prof.M.S. Pavgi Lecture - Methods to test seeds for associated fungi - KHARE, M.N. (Indian Phytopathology, 2002)
Methods for detecting the presence of fungi on and in seeds are described. These include visual inspection either with microscopes or the naked eye, examining seeds under UV or NUV for fluorescence produced by fungi, soaking seeds in water to determine if spores are released from pycnidia, incubation tests and seedling symptom tests. Histopathological, biochemical and immunodiagnostic tests for the detection of fungi are also described.